Clinical Efficacy and Safety of Microwave Ablation Compared to Radiofrequency Ablation in Hepatocellular Carcinoma Patients: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Rifaldy Nabiel Erisadana; Yehuda Tri Nugroho Supranoto; Heni Fatmawati; Irawan Fajar Kusuma; Adrian Wibisono; Putu Ayu Laksmi Lestari (Indonesian Journal of Cancer, 2023)
Background: Ablation modalities for the treatment of hepatocellular carcinoma (HCC) including microwave ablation (MWA) and radiofrequency ablation (RFA) are clinically important due to their numerous advantages. Several trials showed inconsistent results regarding safety and efficacy, making the comparison between MWA and RFA challenging. Therefore, this study aimed to enhance the evidence on treatment modalities regarding the clinical efficacy and safety of MWA compared to RFA in HCC patients. Methods: A systematic review and meta-analysis was conducted following the PRISMA guidelines. Subsequently, a literature search was carried out by PubMed, ScienceDirect, and Google Scholar for randomized controlled trials (RCTs) in HCC patients who passed through MWA compared to RFA. Quantitative analysis of pooled risk ratio with a 95% confidence interval was performed using Review Manager 5.4 software in a random-effects model or fixed-effects model forest plot.Results: Based on 9 RCTs included in the analysis, there were insignificant different results in terms of complete ablation rates (CA) [RR=1.01, 95%CI (0.99 to 1.03), p=0.47] and adverse events (AE) [RR=1.15, 95%CI (0.88 to 1.50), p=0.31]. However, lower incidence of local tumor progression (LTP) [RR=0.73, 95%CI (0.54 to 0.99), p=0.04], intrahepatic de novo lesions (IDL) [RR=0.90, 95%CI (0.81 to 1.00), p=0.05], and extrahepatic metastases (EHM) [RR=0.65, 95%CI (0.44 to 0.95), p=0.03] exhibited significant differences in MWA group.Conclusions: This meta-analysis provided evidence that MWA and RFA had equivalent CA rates and AE in HCC patients. However, MWA was considered superior to RFA due to a lower incidence of LTP, IDL, and EHM.